The relationship between Cytomegalovirusspecific cellular immune response and CD4+ T cell count in HIV positive individuals in a South African setting - Arendse, Germaine Veronique (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScMedSc)--University of Stellenbosch, 2011.